REQUIREMENTS FOR THE DEGREE OF WASTEWATER TREATMENT OF TEXTILE ENTERPRISES OF THE REPUBLIC OF UZBEKISTAN - Mavlanova, Yulduz; Sabirova, Dildora; Axmedova, Feruza (Innovative Development in Educational Activities, 2023)
Technological processes at textile industry enterprises in the Republic of Uzbekistan are very diverse, and therefore the concentrations of impurities contained in industrial wastewater and their qualitative composition can vary widely. Waste water is formed during the processing of raw materials (wool, flax, cotton), bleaching and dyeing of fibers, their reinforcement with adhesives, chemical processing and finishing of fabrics, etc.